2022
DOI: 10.5194/acp-22-11931-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Ambient volatile organic compound (VOC) pollution in urban Beijing: characteristics, sources, and implications for pollution control

Abstract: The increasing ozone (O 3 ) pollution and high fraction of secondary organic aerosols (SOA) in fine particle mass has highlighted the importance of volatile organic compounds (VOCs) in air pollution control. In this work, four intensive field measurements of VOCs during winter of 2018 (from 1 December 2018 to 17 January 2019), spring (15 April to 27 May), summer (17 June to 13 July), and autumn (22 September to 27 November) of 2019 were conducted at an urban site in Beijing to characterize VOC sources and thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…For example, Rad et al (2014) indicated transportation and industry were the primary pollution sources of BTEX in the metropolitan city of Iran [ 31 ]. Cui et al (2012) highlighted the fuel use and diesel exhaust sources of air pollution in Beijing, China [ 32 ]. In Ho Chi Minh City (Vietnam), motorcycles contributed the most to the traffic fleet [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Rad et al (2014) indicated transportation and industry were the primary pollution sources of BTEX in the metropolitan city of Iran [ 31 ]. Cui et al (2012) highlighted the fuel use and diesel exhaust sources of air pollution in Beijing, China [ 32 ]. In Ho Chi Minh City (Vietnam), motorcycles contributed the most to the traffic fleet [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pinthong et al used Positive Matrix Factorization(PMF) to evaluate the source of VOCs and showed that industrial processes and petrochemical industries were the major sources of the VOCs [6]. A study from Beijing also revealed that the main source of VOCs is the vehicle exhaust and industrial emissions [13].…”
Section: Discussionmentioning
confidence: 99%
“…The model configuration is consistent with that of Zheng et al SOAALK represents all alkanes that can generate SOA, mainly composed of C 8 and larger linear or branched alkanes. We assign SOAALK concentration to the concentration of C 8 -alkanes to C 12 -alkanes based on the ratio (0.32, 0.14, 0.08, 0.10, and 0.36) of long-chain alkane concentration measured offline in Beijing (also a polluted urban area) …”
Section: Methods and Datamentioning
confidence: 99%
“…We assign SOAALK concentration to the concentration of C 8 -alkanes to C 12 -alkanes based on the ratio (0.32, 0.14, 0.08, 0.10, and 0.36) of long-chain alkane concentration measured offline in Beijing (also a polluted urban area). 67 Figure S5 illustrates the daily time evolution of the main input data for all of the NPF days. The time resolution for different data may vary from 5 min to an hour.…”
Section: Data Sets and Model Evaluation Protocolsmentioning
confidence: 99%